Application of the Activity-Based Costing to the Logistics Cost Calculation for Warehousing in the Automotive Industry - Tomas Kucera (Communications - Scientific letters of the University of Zilina, 2019)
Activity-based costing is one of the procedures that proved to be very suitable for the financial management of warehouse activities in the automotive industry. Accurate and up-to-date data enables managers to properly plan and manage all the warehousing related activities in the automotive industry. In the activity-based costing approach, overheads costs are allocated in relation to specific logistics activities of the company. The aim of the article is the application of activity-based costing to the logistics cost calculation for warehousing in the automotive industry. The article focuses on the practical application of activity-based costing to the logistics cost calculation for warehousing in the automotive industry to a particular logistics service provider. It highlights the positive and negative use of this method in the practical case study, which is one of the major qualitative scientific methods. The resulting effect of using the activity-based costing method should be to refine the information that is used for the decision-making problems of the top management of the logistics service provider.